English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-30 12:47:30 · 3 answers · asked by alexandra5489 1 in Science & Mathematics Mathematics

3 answers

This is a Quadratic Equation



which is ax^2 + bx + c = 0

x^2 -6x = -6 in the form ax^2 + bx + c = 0 is

x^2 -6x + 6 =0
where
a = 1
b = -6
c = 6

Now Use Quadratic formula

x = (-b +/- Sqrt(b^2 - 4ac))/ 2a

therefore
x = (- -6 +/- Sqrt((-6)^2 - 4(1)(6))/2(1)

x = (6+/- Sqrt(36-24))/2

x = (6+/- sqrt(12))/2

x =( 6+/- 3.46)/2

x = (6 + 3.46)/2 = 9.46/2 = 4.73 and

x = (6 - 3.46)/2 = 2.54/2 = 1.27

hence x = { 4.73, 1.27}

hope you could follow thru what i wrote all the best

2007-01-30 13:35:17 · answer #1 · answered by Anonymous · 1 0

x^2 - 6x = -6

You can't do anything to it in its current form. Quadratics always have to be equated to 0 to solve using conventional methods.

x^2 - 6x + 6 = 0

Now, we use the quadratic formula.

x = [6 +/- sqrt(36 - 4(1)(6)] / 2
x = [6 +/- sqrt(36 - 24)] / 2
x = [6 +/- sqrt(12)] / 2
x = [6 +/- 2sqrt(3)]/2

Now, dividing each term by 2 due to the denominator,

x = 3 +/- sqrt(3)

So our two answers are:
x = {3 + sqrt(3) , 3 - sqrt(3)}

2007-01-30 12:52:11 · answer #2 · answered by Puggy 7 · 0 0

x=1 check replace x in that problem with 1 and it should come out even. It did for me

2007-01-30 12:51:55 · answer #3 · answered by gc2zday 1 · 0 0

fedest.com, questions and answers